Mechanical Recycling of New and Challenging Polymer Systems: A Brief Overview - Vincenzo Titone; Luigi Botta; Francesco Paolo La Mantia (Macromolecular Materials and Engineering)
Abstract Pollution from plastics is a major issue in the current context, prompting the scientific community to focus its efforts on recycling these materials. Mechanical recycling emerges as the most popular due to its practicality and cost‐effectiveness. In fact, with the increase in environmental awareness, the adoption of new circular economy models, stricter regulations mandating disposal and recycling, and lower costs compared to other recycling techniques, this type of recycling is taking a predominant role over other method. However, the presence of a variety of products of different polymeric nature, the introduction of new biodegradable products, and the complexity of multilayer packaging combining different polymers, without concrete solutions for recycling create a heterogeneous range of materials that leaks into the environment. The scientific literature is actively addressing these challenges, and this review aims to explore the latest strategies for enhancing the mechanical recycling of new and challenging polymer systems. Specifically, it explores the recycling of materials originally designated for landfill, incineration or composting, focusing on advancements in management of these previously overlooked and problematic system. This underexplored perspective seeks to offer new insights and innovative solutions that can transform polymer waste management and advance more sustainable recycling practices.